Perceptive analysis of nasal surgery outcomes for headache - C., Sreenivas; Awasthi, Sanjeev Kumar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Headache is the most common symptom requiring visit to a medical practitioner, sinus headache is one of the sub types of headache. Sinus related headaches are curable by surgical methods with a view to restore the functions of the maxilla-ethmo-turbinal ventilation. In this background we conducted a prospective study to investigate the perceptive relief of symptom of proven rhinosinugenic headache in patients undergoing functional endoscopic sinus surgery with septoplasty. Methods: Prospective study, done at a command hospital, Bangalore, a tertiary PG Teaching Hospital during 2010-2011. Even though 200 patients enrolled for the study, only 98 subjects could be assessed at the end of 1 year duration. A patient centric subjective perceptional questionnaire was given preoperatively and then postoperatively on definitive intervals and the patient’s subjective score was tabulated. Results: Rhinosinugenic headache is common amongst 36.73% of the population in the age group of 20 to 30 years age group, followed by 25.5% in the 41 to 50 years age group. Gender distribution- 56% of females in the age group of 31 to 50 years are suffering from headache, and 28% of women in the age group of 31 to 40 years. The most common endoscopic findings were bulla ethmoidalis with a prevalence of 37.75%, followed by middle turbinate anomalies of 31.63%. Conclusions: Endoscopy could not pick up any finding in 8.16% of the study group which was picked up by the non-contrast computerized tomography, perceptive analysis– there was an overall improvement of patient centric headache symptom alleviation of 98% after FESS with septoplasty.